Spider Web Shape of Brass Catalytic Converter for Reducing Exhaust Gas Emission - Hendaryati, Heni; Mokhtar, Ali (Journal of Energy, Mechanical, Material and Manufacturing Engineering, 2017)
The rapid increase of the number of motor vehicles, especially motorcycles, makes serious problem caused by the pollution from gas emission of fossil fuel combustion. The problems related to human health and the erosion on ozone layer is credited to its gas emission. Several dangerous and toxic gasses such as Hydrocarbon (HC), Carbon Monoxide (CO), and Nitrogen Oxide (NOx), Sulphur Dioxide (SO2), and Lead (Pb) are emitted during IC engine operation.To manage those dangerous gasses, catalytic converter which converts the gasses into more eco-friendly CO2H2O and N2 may be employed. In this research, a specially designed catalytic converter made from brass (CuZn) wire in the form of spider web pattern was fitted into exhaust system of a standard motorcycle. The performance of the converter for several engine rotation speeds was examined by measuring CO and HC of exhaust by using Gas Analyzer.By comparing the exhaust of a standard exhaust system and modified exhaust system (fitted with converter), it can be concluded that the converter was able to decrease the exhaust emission gas. For HC content, the percentage of decrease was as much as 36,88 % for converter fitted exhaust system compared to 61.12% for standard one. For CO content, the decrease percentage was 19.90% compared to 80.10% for standard one.